Kajian Usahatani Cabai Merah di Desa Mendalo Indah Kecamatan Jambi Luar Kota Kabupaten Muaro Jambi - Yanita, Mirawati; Rahman, A. (Proceedings Series on Physical & Formal Sciences, 2021)
Red chili is one of the horticultural commodities that are commercially cultivated and become one of the strategic commodities. The commodity is used as a householdfood necessity and a pharmaceutical raw material, although productivity and price often fluctuate. This study aims to (1) Counting the cost and receipt of red chili farming in Mendalo Indah village Jambi district outside the city of Muaro Jambi. (2) Analyzing the large income of red chili farming in Mendalo Indah Village, Jambi District Outside Muaro Jambi Regency. This study used primary data of as many as 50 red chili farmers who were taken deliberately (purposive), considering that only Mendalo Indah Village was conducting sustainable red chili farming activities in the Jambi district outside the city. The method of population retrieval used in this study is by census method. The data analysis method used quantitative analysis. Based on the results of the research obtained that the average total cash cost is Rp 16,905,304/farmer/MT and Rp 23,359,273/ha/MT and the unpaid fee (taken into account) is Rp 8,255,687/farmer/MT and Rp 12,322,293/ ha/MT. The average revenue obtained by farmers is Rp 98,071,560/farmer/MT and Rp.146,294,776/ha/MT. so that the average income amounted to Rp 81,166,256/ farmer/MT and Rp 121,143,605/ha/MT. In the future, farmers are expected to manage agricultural inputs by implementing good agricultural practices to increase productivity further.